FIE2: a program for the extraction of genomic DNA sequences around the start and translation initiation site of human genes - Chong, Allen (Oxford University Press, 2003)
FIE2 (5′ end Information Extraction v2) is a web-based program for easy identification and extraction of nucleotide sequence around the start of genes (promoter region) and their translation initiation site (TIS). Using information provided by the National Center for Biotechnology Information's (NCBI's) LocusLink, FIE2 identifies the 5′-most end of a gene on its respective chromosome based on alignment of a selected set of mRNAs representative of the gene. FIE2 then uses currently available human genome sequence information to extract the desired sequences. The accuracy of the information extracted is therefore limited by the accuracy and completeness of the sequence annotation and sequence alignment provided by LocusLink. In addition, multiple TIS positions are also occasionally presented, for example, as a result of multiple alignments of transcript variants. One of the key criteria of FIE2 is that it should extract only the correct information or attempt no extraction at all. To date, the authors are not aware of any publicly available web-based tool that uses the human genomic sequence to extract pertinent promoter- and TIS-region information in this fashion. FIE2 is freely available at http://sdmc.lit.org.sg/FIE2.0.